Influence of social distancing on physical activity among the middle-aged to older population: Evidence from the nationally representative survey in China - Wuping Zhou; Lanyue Zhang; Ting Wang; Qiaosheng Li; Weiyan Jian (Frontiers Media S.A., 2022)
BackgroundGroup-based physical activity is an important positive factor assisting the middle-aged to older population to be regularly physically active, especially inside a society with a large population and highly sociable environment. However, when group-based physical activity is restricted during a public health crisis such as the infectious disease pandemic, the influence of social distancing on physical activity among this vulnerable group needs to be recognized.ObjectivesThis study aimed to investigate the influence of social distancing on physical activity among the middle-aged to older Chinese population at the national level.MethodsData from a nationally representative social follow-up survey (China Family Panel Studies, CFPS) for 2018 and 2020 were used. Physical activity level in year 2018 was set as the baseline to be compared with that for each individual in 2020, when China implemented social distancing during the COVID-19. Chinese population with an age greater than 45 years were included, and three levels of physical activity were established. Logistic models were developed to identify sociodemographic characteristic that may be associated with a higher probability of worse PA behaviors during the social distancing.ResultsOver 46% respondents could be described as being Physically Inactivity during 2018 and this proportion increased to 67.2% in 2020. Respondents who live in the Northeast or rural regions, having a spouse, being employed, having a low level of education, and being of low-income level showed a higher decrease in physical activity compared to other groups. However, individuals living with chronic diseases emerge as being more likely to maintain positive habits with respect to physical activity in this context.ConclusionSocial distancing during the COVID-19 pandemic has significantly influenced the extent of physical activity among middle-aged to older Chinese residents. This is especially true in respect to middle-aged and elderly people who are at increased risk of chronic diseases. Given this, there is a clear need to consider effective modalities for physical activity in the context of social distancing based on home quarantine and city lockdown. Furthermore, specific health-related strategies need to be considered in relation to different regions and populations.